Karakterisitik Edible Film Berbahan Whey Dangke dengan Penambahan Karagenan (CHARACTERISTICS OF EDIBLE FILM BASED DANGKE WHEY WITH CARRAGEENAN ADDITION) - Maruddin, Fatma; Ratmawati, Ratmawati; Fahrullah, Fahrullah; Taufik, Muhammad (Jurnal Veteriner; Vol 19 No 2 (2018), 2018)
Dangke whey is one type of protein and can be made edible film. The quality of the edible film made from dangke whey can be improved with the addition of carrageenan. The purpose of this research was to determine the quality of the edible film made from dangke whey with the addition of different concentrations of carrageenan. The qualities of the edible film observed were the microstructure, the color values L *, a * and * b, water vapor transmission rate (WVTR) and thickness. Data analyzed using ANOVA with a completely randomized design. The treatment used of carrageenan with different concentrations: 2%; 2.5%; 3% and 3.5%. Each treatment was repeated 3 times. Microstructure of edible film showed the improvement of interaction between the molecules of constituent materials. Values of color* L were 86.1088.37, the value of color * a were -0.55-0.70 and a value of the color * b were 2.03-3.35. Water vapor transmission rate (WVTR) were 5.08-5.35 g/mm2.jam. The thickness were 0.034-0.036 mm. The use of carrageenan concentrations up to 4% for manufacturing of edible film have not changed for the color * L, * a and * b, the rate of water vapor transmissions and thickness. Based on the microstructure showed that the molecules of edible film properly distributed beginning on the use of carrageenan concentration of 2.5%.